Increased mortality in a Danish cohort of young people with Type 1 diabetes mellitus followed for 24 years. Issue 3 (21st April 2016) - Sandahl, K.; Nielsen, L. B.; Svensson, J.; Johannesen, J.; Pociot, F.; Mortensen, H. B.; Hougaard, P.; Broe, R.; Rasmussen, M. L.; Grauslund, J.; Peto, T.; Olsen, B. S.
Abstract: Aim: To determine the mortality rate in a Danish cohort of children and adolescents diagnosed with Type 1 diabetes mellitus compared with the general population. Methods: In 1987 and 1989 we included 884 children and 1020 adolescents aged 20 years and under, corresponding to 75% of all Danish children and adolescents with Type 1 diabetes, in two nationwide studies in Denmark. Those who had participated in both investigations ( n = 720) were followed until 1 January 2014, using the Danish Civil Registration System on death certificates and emigration. We derived the expected number of deaths in the cohort, using population data values from Statistics Denmark to calculate the standardized mortality ratio. Survival analysis was performed using Cox proportional hazards model. Results: During the 24 years of follow‐up, 49 (6.8%) patients died, resulting in a standardized mortality ratio of 4.8 (95% confidence interval 3.5, 6.2) compared with the age‐standardized general population. A 1% increase in baseline HbA1c (1989), available in 718 of 720 patients, was associated with all‐cause mortality (hazard ratio = 1.38; 95% confidence interval 1.2, 1.6; P < 0.0001). Type 1 diabetes with multiple complications was the most common reported cause of death (36.7%). Conclusion: We found an increased mortality rate in this cohort of children and adolescents with Type 1 diabetes compared with the general population. The only predictor for increased risk of death up to 24 years after inclusion was the HbA1c level in 1989. This emphasizes the importance of achieving optimal metabolic control in young people with Type 1 diabetes. What's new?: We included 75% of all children and adolescents with Type 1 diabetes in Denmark in 1989 and followed them for 24 years using high‐quality registries. We confirmed that Type 1 diabetes is associated with a higher mortality than the general population, with an almost five times increased standardized mortality ratio. Among our patients, HbA1c was the only significant covariate predicting death, with a 38% increase in risk of death for every 1% increase in HbA1c. We observed that Type 1 diabetes with multiple complications was the most frequently reported cause of death in this cohort.